(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
Market transition to free trade agreement encourages Indonesia to improve foreign trade performance through stabilization of market position in the international market. The aims of this research were to analyze the competitiveness of coffee, cocoa, palm oil and rubber products in the international market, and to analyze Indonesia’s export dynamic in ASEAN and European markets. This research was conducted by analyzing secondary data particularly export data from 2010 to 2015. Revealed Comparative Advantage (RCA) and Constant Market Share (CMS) approaches were used to analyze export competitiveness of Indonesian products in the world market. The results showed that Indonesian agricultural products (coffee, cocoa, palm oil and rubber) had a comparative advantage over the average rate of world (RCA > 1), except natural rubber products. Meanwhile, CMS analysis indicated that dynamic of Indonesian export was more affected by export growth and product composition effects, than that of market distribution and competitiveness effects. It revealed that Indonesia responded less to market demand in terms of quality, import growth of export destination countries and market intelligence related to competitor market positioning.